STRATEGI INDONESIA DALAM MENGATASI MASUKNYA KOSMETIK ILEGAL DARI MALAYSIA TAHUN 2015-2019 - Chyntania Anggreni Laia; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to explain the strategy of the Indonesian government in overcoming the entry of illegal cosmetics into Indonesian territory. The entry of illegal cosmetics is due to globalization and free trade which provide wide space for the flow of goods and services transactions that cross the borders of a country. BPOM as the agency authorized to supervise cosmetics in circulation often gets illegal cosmetics circulating in Indonesian territoryThe Study uses a qualitative research method, with the level of analysis of the nation state. The author use the theory of Strategy with the concept of Non- Traditional Security using the perspective of Constructivism. To analyze this problem, the authors collected data from books, journals, websites, dictionaries, reports, data from the Drug and Food Monitoring Agencies about illegal cosmetics  from Malaysia.The Finding of this study indicates that the strategy carried out by the Indonesian Government is to control by the BPOM and strengthen the applicabale laws. Apart from that, in overcoming illegal cosmetics, Indonesia is also conducting regional cooperation as well as international cooperation. The cooperation carried out is security cooperation by strengthening guarding in border areas, as well as working with ASEAN through the Post Market Alert System (PMAS) activity. Keyword: Indonesia, Non- Tradisional Security, Illegal Cosmetics, Strategy.